Deep-ploughing reduced nutrient contents in plough layer of paddy field-a case study of Hunan Province, China. Issue 1 (December 2020) - Xiao, Y S; Gao, Z Q; Cao, Z H; L, W J; Li, H G; He, B; He, Z H; Zhong, Q
Abstract: In this study, the data of the typical paddy fields from 63 soil series of hydragric anthrosols (paddy soil) and 26 paddy fields under tobacco-rice rotation in Huan province of China were used to assess the current thickness of the plough layers of the paddy fields, set up the criterion of deep-ploughing (30 cm in this study) feasibility for the paddy fields, and predict the possible changes of soil nutrient contents in the new plough layers after deep-ploughing. The results showed that the mean thickness of current Ap1 was 15.3 cm, and 93.2% of the paddy fields were lower than the ideal depth of 20 cm. The criterion of deep-ploughing feasibility was established by comparing the textures and bulk densities of the plow-pan (Ap2) and the below adjacent hydragric horizon (Br1), i.e., Br1 is not finer than Ap2 in texture and more compacted than Ap2 in bulk density, and was preliminarily validated by a real deep-ploughing test. 69.8% of the paddy fields were feasible to deep-ploughing according to the proposed feasibility criterion. The contents of main nutrients would be significantly decreased after deep-ploughing, which indicate more fertilizers should be applied after deep-ploughing in order to maintain and promote soil fertility and the crop yields.